The evolution of the performance in the international and national women#s pole vault - Ionescu, M. (2000)
The performance in European women's pole vault starts with '80 years. This event developed after the women's triple jump official competitions. Starting with 1990 it appear like a demonstrative event during the national competitions, but only from 1994 the world's record has been registered. From this moment the women's pole vault was recognised as an official event for indoor and outdoor European Championships and World Championships and this it will be present as an official athletic event at the Sydney Olympiad. From it appearance till now days, the results have been improved, as the number of participation, too.